Labial hypertrophy as a cause for vulvae pruritis - Firdaus, Arshiya; Chaudhary, Rachna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Labia minora hypertrophy is a relatively uncommon surgical condition being popularised in the realm of vulvovaginal plastic surgeries. Apart from the unaesthetic appearance of the hypertrophied minora, these cases are also associated with itching, hygiene problem, pain while sitting down, sports activities, difficulty in wearing tight clothing, bleeding and discomfort while or after sexual intercourse, social embarrassment, insecurity and psychological diminution of confidence and self‐esteem. In a country like India, due to sociocultural reasons, patients hesitate to consult a doctor for such deformities. Most of the patients suffer in silence for years. Although common in the west, very few surgeons in the country perform this simple and rewarding surgery. Here, presenting a case of married women of reproductive age group presented to the study side with complains of severe vulvar itching, the cause of itching was labia minora hypertrophy.